2019
DOI: 10.1038/s41598-019-44279-z
|View full text |Cite
|
Sign up to set email alerts
|

An optimal BMI range associated with a lower risk of mortality among HIV-infected adults initiating antiretroviral therapy in Guangxi, China

Abstract: Previous studies investigating HIV-infected patients suggested a direct link between underweight and the mortality rate of AIDS. However, there was a lack of evidence showing the optimal range of initial body mass index (BMI) patients maintain during antiretroviral therapy (ART). We aimed to evaluate associations of the BMI values pre-ART and during the entire ART duration with mortality among HIV-positive individuals. In total, 5101 HIV/AIDS patients, including 1439 (28.2%) underweight, 3047 (59.7%) normal-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…In recent years, many researchers have reported that some laboratory indicators are connected with the survival rate of PLHIV. In this study, CD4, BMI and GLU were signi cantly correlated with the survival rate of PLHIV and showed good consistency with these published studies [10,16,21,26] .…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, many researchers have reported that some laboratory indicators are connected with the survival rate of PLHIV. In this study, CD4, BMI and GLU were signi cantly correlated with the survival rate of PLHIV and showed good consistency with these published studies [10,16,21,26] .…”
Section: Discussionsupporting
confidence: 89%
“…Before ART's availability, HIV infected patients with higher BMI showed slower HIV progression compared to underweight patients (128,129), presumably due to delayed wasting/cachexia effects. In ARTtreated patients, obese or underweight patients exhibited higher cumulative mortality rates, delineating an optimal BMI range between 24 and 28 (130) and obesity has been identified as a risk factor for multimorbidity (131). Regarding the impact of obesity on CD4 T cell reconstitution, patients with higher BMI before ART initiation exhibit higher (132,133) or comparable (134) immune reconstitution.…”
Section: An Important Factor: the Host Metabolic Status Prior Infectionmentioning
confidence: 99%
“…Guangxi, a province in southwestern China, has the second highest number of reported HIV cases in the country, with 703,000 survivals and 40,500 deaths by 2017. The mortality rate (34.3% [4] ) was also higher than the national average mortality rate (23.8%) during the same period. In China, the National Free Antiretroviral Treatment Program (NFATP) began in 2002 and was scaled up in 2003.…”
Section: Introductionmentioning
confidence: 64%